Government budget deficits in large open economies - Willem H. Buiter; Anne C. Sibert (Center for Economic Studies and ifo Institute (CESifo), 2011)
Large and growing levels of public debt in the United States, United Kingdom, Japan and the Euro Area raise new interest in the cross-country effects of a large open economy's deficits. We consider a dynamic optimising model with costly tax collection and exogenously given public spending and initial debt. We ask whether the externalities associated with an individual country's deficits are positive or negative. We characterise the path of taxes in the Nash equilibrium where policy makers act nationalistically and compare this outcome to the global optimal outcome.
Keywords: E62; F42; H21; 330; fiscal policy; international policy coordination; optimal taxation; Haushaltsdefizit; Offene Volkswirtschaft; Finanzpolitik; Steuerpolitik; Internationale wirtschaftspolitische Koordination; Optimale Besteuerung; Theorie